2014
DOI: 10.5414/cn107786
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous bilateral perirenal hemorrhage following prolonged fever: an uncommon presentation of polyarteritis nodosa

Abstract: A 68-year-old man presented with a spontaneous bilateral perirenal hemorrhage following a 2-month fever of unknown origin. A renal biopsy for a pathologic diagnosis seemed very risky because of the patient's bilateral perirenal hemorrhage. Therefore, we diagnosed polyarteritis nodosa using an abdominal computed tomography scan, a renal angiogram, and American College of Rheumatology criteria. The patient's multiple symptoms then responded well to the prescribed immunosuppressive regimen. This case is an uncomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The precise frequency and pathophysiology of spontaneous aneurysm healing in PAN is unknown. Our review of the literature identified 81 reports of PAN patients who presented solely with acute disease limited to the intraabdominal cavity, 43 of which had Wunderlich's syndrome [5][6][7][8][9][10][11][12][13][14][15][16][17]. Therefore, when managing patients with spontaneous, atraumatic intra-abdominal hemorrhage in the absence of a mass or bleeding diathesis, PAN should be placed high on the list of diseases to exclude.…”
Section: Discussionmentioning
confidence: 99%
“…The precise frequency and pathophysiology of spontaneous aneurysm healing in PAN is unknown. Our review of the literature identified 81 reports of PAN patients who presented solely with acute disease limited to the intraabdominal cavity, 43 of which had Wunderlich's syndrome [5][6][7][8][9][10][11][12][13][14][15][16][17]. Therefore, when managing patients with spontaneous, atraumatic intra-abdominal hemorrhage in the absence of a mass or bleeding diathesis, PAN should be placed high on the list of diseases to exclude.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Cases of SRH are a diagnostic challenge due to either the nonspecific signs of acute onset flank pain, palpable mass, and hypovolemia (Lenk's triad), or even less specific signs, such as lethargy and pyrexia. 1,3,5,6 Advanced imaging modalities are required to diagnose the underlying etiology. 1,3,5 Within the veterinary literature, to the authors' knowledge, there is only a single report of unilateral SRH of unknown etiology, 7 with all others being associated with neoplasia 8 or trauma.…”
Section: Introductionmentioning
confidence: 99%